2008
DOI: 10.1002/jmv.21277
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Persistent cytomegalovirus (CMV) infection after haploidentical hematopoietic stem cell transplantation using in vivo alemtuzumab: emergence of resistant CMV due to mutations in the UL97 and UL54 genes

Abstract: Addition of in vivo alemtuzumab to the conditioning regimen enabled 2- or 3-locus-mismatched hematopoietic stem cell transplantation with an acceptable incidence of graft-versus-host-disease. However, the procedure was associated with a high incidence of cytomegalovirus (CMV) reactivation. Although preemptive therapy with ganciclovir prevented successfully severe CMV diseases and CMV-related mortality, a patient developed persistent positive CMV antigenemia for more than 1 year after transplantation and CMV di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…A patient with myelodysplastic syndrome developed persistent CMV antigenemia after hematopoietic stem cell transplantation, and CMV was isolated after treatment with ganciclovir and foscarnet. CMV was resistant to ganciclovir and foscarnet but sensitive to cidofovir and had mutations in UL97 (A594V) and UL54 (Q578H) (Oshima et al, 2008). This UL97 mutant was used as UL97 mutant A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A patient with myelodysplastic syndrome developed persistent CMV antigenemia after hematopoietic stem cell transplantation, and CMV was isolated after treatment with ganciclovir and foscarnet. CMV was resistant to ganciclovir and foscarnet but sensitive to cidofovir and had mutations in UL97 (A594V) and UL54 (Q578H) (Oshima et al, 2008). This UL97 mutant was used as UL97 mutant A.…”
Section: Methodsmentioning
confidence: 99%
“…a Clones 14 and 46 were mizoribine-resistant clones isolated after culture for 3 months in the presence of 100 g/ml mizoribine. b UL97 mutants A and B were clinical isolates resistant to ganciclovir and had mutations in UL97 (A594V) and UL54 (Q578H) (Oshima et al, 2008) and UL97 (L595S), respectively.…”
Section: Susceptibility Of Ganciclovir-resistant Clinical Isolates Anmentioning
confidence: 99%
“…The resultant supernatants were used as the cell-free virus stocks, and their virus titers ranged from 3.3 ϫ 10 3 to 2.3 ϫ 10 5 PFU/ml in this study. The Towne strain of cytomegalovirus (CMV) (18,28) and rhinovirus 13 (13) were propagated in HEL cells, and adenovirus 5 (19) was propagated in Hep2 cells. CMV, rhinovirus 13, and adenovirus 5 were prepared from the infected cells by three cycles of freezing and thawing.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…However, alemtuzumab-based conditioning is associated with strong immune suppression and a delayed immune reconstitution after transplantation, which might lead to higher incidence of CMV reactivation. 29 Another possible disadvantage of alemtuzumab is that it might eliminate NK cells, which might be important for a GVM effect. 30 Koh et al reported that the lympholytic effect of alemtuzumab on NK cells was weaker than that on T cells and the use of alemtuzumab for ex vivo T cell depletion-alemtuzumab "in the bag"-resulted in the 99.8% and 94% depletion of CD4+ and CD8+ T cells, respectively, whereas 30% of NK cells were conserved in the graft.…”
Section: Alemtuzumab-based Conditioning Regimenmentioning
confidence: 99%